MULTIKULTURALISME DAN IMPLEMENTASINYA DALAM DUNIA PENDIDIKAN (KAJIAN QUR’AN DAN HADITS) - Ade Mandala; Umi Sumbulah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to examine multiculturalism from the perspective of the Qur’an and Hadith and how it is implemented in the world of education. This research uses library research. The results of this research show that many verses from the Qur’an and Hadith explain diversity, including race, ethnicity, nation, language, and even religion. However, this diversity is not meant to bring each other down, but rather to get to know each other's. Thus, it is clear that long before the word